(untitled) (Research, Society and Development, 2021)
In the Brazilian Amazon, forest fragments increase annually leading many species to local extinction. Euxylophora paraensis Huber is an endemic species whose natural habitat is restricted to the north of Brazil. The natural regeneration was evaluated using 10 circular plots of land each with a radius of 20 meters. The density of regenerating individuals at the edge and the interior of the fragment and the behavior in relation to the parent tree. The Periodic Annual Increment of the diameter and the height were calculated individually for each plant that remained alive during all four measurements and GLM (General Linear Model) was applied to verify if there were differences between environments and the size of the individuals. The results show that the density of natural regeneration increases as the distance from the parent tree increases and has a significant negative correlation with canopy area, the smaller the canopy area the higher the density of individuals. Larger diametric growth was observed in saplings and small trees at the edge and larger increments of height in small trees were observed both at the edge and interior of the fragments. Therefore, natural regeneration is influenced by the process of forest fragmentation where the germination of seeds and establishment of saplings is favorable, however, there were no adult trees at the edge.